Economic valuation of environmental goods and services - Matos, Alda (2011)
The economic valuation of environmental goods and services (EVEG&S) results of the increasing concern with the quality of industrial products and the reduction of social welfare. The EVEG&S presents the direct and indirect costs and benefits of quantitative and qualitative environmental changes in goods and services and corresponding impacts. This is particularly important in the valuation of investment projects and governmental policies. This study consists in a survey of environmental appraisal methods, focusing into the hypothetical and complementary market based ones. The review reveals that evaluation of environmental quality is very complex. In fact, for each criterion there are several assumptions that are inapplicable to all situations. Effectively, despite the evident complementarity of conventional goods environmental quality, the values attributed to these resources could be underestimated and complementary and substitute markets can be inefficient parameters.